Long‐term outcomes of rituximab therapy in pemphigus. (9th July 2020) - Shimanovich, I.; Baumann, T.; Schmidt, E.; Zillikens, D.; Hammers, C.M.
Abstract: Background: Rituximab induces a rapid remission in most patients with pemphigus. Objective: Our aim was to assess the long‐term efficacy of rituximab in this disease. Method: We conducted a retrospective study of 59 patients with pemphigus treated with rituximab and observed over a median period of 104 months. Results: The rate of complete remission off therapy (CRoff) after the first rituximab cycle was 39%, increasing to 61% with additional rituximab courses. Long‐term CRoff was achieved in 27% of patients. The recurrence rate after the first rituximab cycle was 63%, decreasing to approximately 40% with subsequent rituximab cycles. Median time to relapse after the first and subsequent rituximab cycles was 25 months. Renewed rituximab therapy reinduced complete remission in 94% of cases. Baseline anti‐desmoglein antibody levels of ≤250 U/mL were significantly associated with the outcome of CRoff. In paired serum samples obtained before the first and six months after the last rituximab therapy, significant reductions of desmoglein‐specific autoantibodies were observed. Patients relapsing after a complete remission induced by the first rituximab cycle were more likely to achieve CRoff than patients relapsing after a less favourable outcome and non‐responders. There was no significant difference in age, sex, pemphigus subtype, rituximab dosing and disease duration between patients achieving CRoff and those not meeting this end point. Conclusions: Lower desmoglein‐specific antibody levels at baseline were predictive of CRoff. In patients receiving multiple rituximab cycles, complete remission after the first cycle was associated with a favourable long‐term outcome. Repeated rituximab courses were highly effective for relapsed disease and improved the overall outcome.